Original researchScreening for coeliac disease among Egyptian children - Abd El Dayerm, Soha M.; Ahmed Aly, Azza; Abd El Gafar, Esmat; Kamel, Hesham (Archives of Medical Science, 2010)
Introduction: To screen for coeliac disease in Egyptian children with non-endocrinal short stature, refractory iron deficiency anaemia and type 1 diabetes. Also, to evaluate the sensitivity and specificity of different serological tests for diagnosis of coeliac disease (CD). Material and methods: The study included 292 patients with clinical risk of CD. Testing for coeliac antibodies was performed, together with upper gastrointestinal endoscopy and small intestinal biopsy. Results: Eleven patients (44%) among 25 patients with refractory iron deficiency anaemia, 23 patients (34.3%) among 67 patients with non-endocrinal short stature, and 6 patients (3%) among 200 patients with type I diabetes mellitus were diagnosed by jejunal biopsy as having coeliac disease. AGA (IgG) had the highest sensitivity for diagnosing CD (80.0%) followed by the TTG (72.7%) antibody, while ARA had the highest specificity (95.9%) followed by anti-EMA (94.7%). Conclusions: Coeliac disease is more common in Egyptian children with refractory iron deficiency anaemia, non-endocrinal short stature and type 1 diabetes than was previously thought; therefore it is mandatory to screen such patients for CD. Serological tests showed fairly good sensitivity and specificity for the diagnosis; however, intestinal biopsy remains the cornerstone for definitive diagnosis of patients with immunological reaction to gluten.